Systemic Oxidative Stress and Conversion to Dementia of Elderly Patients with Mild Cognitive Impairment. (12th January 2014) - Cervellati, Carlo; Romani, Arianna; Seripa, Davide; Cremonini, Eleonora; Bosi, Cristina; Magon, Stefania; Bergamini, Carlo M.; Valacchi, Giuseppe; Pilotto, Alberto; Zuliani, Giovanni
Abstract : Mild cognitive impairment (MCI) is regarded as a prodromal phase of late onset Alzheimer's disease (LOAD). It has been proposed that oxidative stress (OxS) might be implicated in the pathogenesis of LOAD. The aim of this study was to investigate whether a redox imbalance measured as serum level of hydroperoxides (i.e., by-products of lipid peroxidation) and/or serum antioxidant capacity might be predictive of the clinical progression of MCI to LOAD. The levels of these two markers were measured in 111 patients with MCI (follow-up: 2.0   ±   0.6 years), 105 patients with LOAD, and 118 nondemented healthy controls. Multivariate analysis adjusted for potential confounding factors, including age, gender, smoking, and comorbidities, showed a significant increase (P < 0.05 ) in baseline levels of OxS in MCI and LOAD as compared to cognitive healthy controls. No differences in either of OxS markers were found by comparing MCI patients who converted (n   =   29 ) or not converted (n   =   82 ) to LOAD. Overall, these results suggest that systemic OxS might be a precocious feature of MCI and LOAD. However, the role of OxS as an early prognostic marker of progression to LOAD needs further investigations.